Communication Gap and Public Perception: A Case Study of Smart City Implementation in Banjarmasin - Waluyo, Bambang Dwi; Aldi Istihsan, Muhammad (Universitas Medan Area, 2025)
Banjarmasin City was named one of Indonesia's top 20 Smart Cities in 2023. However, this achievement contrasts with the poor functionality and limited usability of the super apps developed by the city government. This study analyzes how the Banjarmasin City Government communicates the success of its Smart City program and explores why many citizens remain dissatisfied with the digital services provided. Drawing on Ulber Silalahi's theory of government communication, the research reveals a significant gap between public expectations and the actual implementation of Smart City initiatives. While the government has tried to improve its services, it lacks a thorough mechanism for collecting citizen feedback. Moreover, the absence of collaboration with the private sector in developing and managing the super apps further hinders progress. The findings suggest that more inclusive communication strategies and stakeholder engagement are needed to align the city's Smart City vision with the experiences of its residents.